Vector Model Standardization of Standards with Dual DSP Cod - Vladimir Krizaic (Scientific Research, New Technologies and Applications Vol. 9, 2024)
The digital revolution extends not only to technology but also to the organization and management of complex processes that are essential for the development of projects, with the aim of improving the economic principles of the operation of business systems. However, it has been found that there are no great advances in productivity because the old standardization, calculation and tendering system is copied into ICT technology, which does not affect the performance of the system. Then, despite digitization, the problem of the cumbersomeness and inaccuracy of linking standards to define calculations and plans for process and construction production remains due to the obsolescence and static nature of standards and cost lists. Therefore, the recommendation is to change the model of the organizational structure to a vector organization, which has been upgraded to a process system as a by-product of the computerization of the economy and production. Vector standardization of standards (MSN) is also proposed for the model standardization of the offer or project with a dual code called dynamic structural programming or dual DSP code. The Krizaic DSP method is a logical induction equation which, in cooperation with vector standards and a modified Gaussian MGSC equation, establishes the infinity and uniqueness of the process product. The extension or connection with BIM and digital twins creates an AI system for project management.